Clinical practice guidelines for the management of conditions related to traffic collisions: a systematic review by the OPTIMa Collaboration. (25th June 2014) - Wong, Jessica J.; Côté, Pierre; Shearer, Heather M.; Carroll, Linda J.; Yu, Hainan; Varatharajan, Sharanya; Southerst, Danielle; van der Velde, Gabrielle; Jacobs, Craig; Taylor-Vaisey, Anne
Abstract: Objective : To evaluate the methodological quality and synthesize recommendations of evidence-based guidelines for the management of common traffic injuries. Study design : We conducted a systematic review and best evidence synthesis of guidelines on musculoskeletal injuries, psychological disorders and mild traumatic brain injuries (MTBI) from 1995 to 2012. Independent reviewers critically appraised eligible guidelines using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) criteria. Results : We retrieved 9863 citations. Of those, 16 guidelines were eligible for critical appraisal and eight were scientifically admissible (four targeting whiplash-associated disorders (WAD), one addressing anxiety and three addressing MTBI). The inadmissible guidelines had inadequate literature searches, inexplicit links between evidence and recommendations, and ambiguous recommendations. The literature used to develop most of the admissible guidelines was outdated. Major recommendations included: (1) Advice, education and reassurance for all conditions; (2) Exercise, return-to-activity, mobilization/manipulation, analgesics and avoiding collars for WAD; (3) Psychological first aid, pharmacotherapy and cognitive behavioral therapy as first-line interventions for anxiety; and (4) Monitoring for complications, discharge criteria, advice upon discharge from the emergency room and post-discharge care for MTBI. Conclusion : Fifty percent of appraised guidelines were scientifically admissible, but most need updating. Most guidelines focus on WAD and MTBI. Few guidelines make comprehensive recommendations on a wide range of consequences from traffic collisions. Implications for Rehabilitation: The core components of a program of care designed to manage common traffic injuries (whiplash-associated disorders – WAD, anxiety and mild traumatic brain injuries) should include advice, education and reassurance. Depending on the condition, the following specific interventions should be considered: (1) WAD: exercise, early return to activity, mobilization/manipulation, analgesics and avoidance of collars; (2) Anxiety: psychological first aid, pharmacotherapy and cognitive behavioral therapy; and (3) Mild traumatic brain injuries: use of specific discharge criteria (including no factors warranting hospital admission and support structures for subsequent care), education upon discharge from emergency room and post-discharge care (e.g. monitoring for complications, gradual return to normal activity based on tolerance of individual). The methodological quality of guidelines varies greatly; therefore, guideline developers need to adhere to established methodological standards and conform to the evaluation criteria outlined in the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument.